3G, HSPA AND 4G LTE Network Reliability and Achievable Internet Speeds on Airborn Aircraft up to 10.000 FT Above Ground Level - Subotič, Ilija (Informatica, 2023)
Nowadays, we are witnesses of 5G mobile technology advancements and many countries plan to or already have introduced this technology to public usage. However, the older technologies such as 3G, HSPA and 4G LTE, because of their physical properties, ways of datagram transfers and frequency bands used, are still very suitable for usage in cases that assume longer distances between terminal device and cell towers. Having that in mind, a research was conducted during 2021. and 2022. in order to test i.e. verify or refute the hypothesis that 3G, HSPA and 4G LTE technologies will be reliable enough to provide a satisfactory connection on aircraft flying up to 3 km (10.000 ft) above ground level, quality enough to establish Internet connection speeds of at least 1Mbps, which would be enough to serve as a medium for innovated, Internet-based data links similar to CPDLC/ACARS. Through a series of 14 airplane flights, both above plains and mountain regions, first-hand data was gathered and analyzed accordingly, so reliable conclusions about presented hypothesis could be made. Empirical research results were accompanied with research results made on well-known computer radio propagation simulator TAP7.